Existential Vacuum and External Locus of Control as Predictors of Burnout among Nurses. - Alfuqaha, Othman A.; Al-olaimat, Yazan; Abdelfattah, Ahmad Sami; Jarrar, Rand Jamal; Almudallal, Bashar Mazin; Abu ajamieh, Zaid Ibrahim (Nursing Reports, 2021)
Existential vacuum and psychological burnout are becoming increasingly important issues in healthcare professions, especially nursing. This study aimed to investigate the contribution of several demographic factors including gender, work position, experience, and educational level as well as existential vacuum and locus of control (external and internal) in predicting burnout among nurses. A convenience sample of 181 nurses was selected to represent the study sample. Participants were assessed using an existence scale, locus of control scale, and burnout scale. The study showed that 40.3% of nurses had severe existential vacuum. It was found that 93.9% of nurses had experienced a moderate level of burnout. External locus of control was the most common personality trait among participating nurses in this study. It also was found that existential vacuum and external locus of control were the main predictors of psychological burnout among nurses. The findings of our study highlight major problems facing nursing, such as existential vacuum and psychological burnout. It is recommended to enhance nurses' workplace, provide proper psychological prevention programs, and teach advocacy skills.